Language diversity and thought a reformulation of the linguistic relativity hypothesis - Lucy, John Arthur 1949- (Studies in the social and cultural foundations of language, 1992)
Language Diversity and Thought examines the Sapir–Whorf linguistic relativity hypothesis: the proposal that the grammar of the particular language we speak affects the way we think about reality. Adopting an historical approach, the book reviews the various lines of empirical inquiry which arose in America in response to the ideas of anthropologists Edward Sapir and Benjamin L. Whorf. John Lucy asks why there has been so little fruitful empirical research on this problem and what lessons can be learned from past work. He then proposes a new, more adequate approach to future empirical research. A companion volume, Grammatical Categories and Cognition, illustrates the proposed approach with an original case study. The study compares the grammar of American English with that of Yucatec Maya, an indigenous language spoken in southeastern Mexico, and then identifies distinctive patterns of thinking related to the differences between the two languages